Simple method for estimation of effectiveness in one tube pass and one shell pass counter-flow heat exchangers - Bahadori, Alireza (Elsevier, 2011)
In one tube pass and one shell pass counter-flow heat exchangers, when both streams change temperature by different amounts, the effectiveness is defined as the temperature change for the stream with lower capacity divided by the maximum possible change and the effectiveness depends on the number of transfer units and the thermal capacity ratio. In this paper, an attempt has been made to formulate a simple-to-use method which is easier than existing approaches, less complicated and with fewer computations for accurate and rapid estimation of effectiveness in one tube pass and one shell pass counter-flow heat exchangers as a function of number of transfer units and the thermal capacity ratio. The proposed method permits estimating the exit temperature for a one tube pass and one shell pass counter-flow heat exchanger without a trial-and-error calculation. The average absolute deviations between the reported data and the proposed correlations are found to be less than 2% demonstrating the excellent performance of proposed correlation. The tool developed in this study can be of immense practical value for engineers and scientists to have a quick check on the effectiveness in one tube pass and one shell pass counter-flow heat exchangers at various conditions without opting for any experimental measurements. In particular, practice engineers would find the predictive tool to be user-friendly with transparent calculations involving no complex expressions.